Profile ultrasound fetal lung maturity - Guivovich, Alex (2015)
OBJECTIVE. To predict intrauterine fetal pulmonary maturity through certain ultrasound parameters in order to avoid potential risks inherent to invasive and more expensive procedures, like amniocentesis and phospholipids determination. METHOD. Clinical and experimental study to determine hoth predictive value and sensitivity of this diagnostic procedure. RESULTS. Prospective study of 5O non-diabetic and non-Rb sensitized high-risk pregnant women with delivery before 48 hours from the last ultrasound control; evaluation of perinatal result. Ten cases were preterm pregnancies, gestational age was 30 to 38 weeks at delivery. Best correlation with pulmonary maturity were the following: placenta grade III, distal femoral and proximal tibial epiphysis 11 cm, presence of proximal humerus epiphysis, renal length above 40 mm, lung/liver ultrasound relation above 1, intestinal status 3 or 4 and combined Salman 5 parameters score of 5. CONCLUSIONS. Use of the combination of ultrasound findings is rational and safe to predict fetal pulmonary maturity, avoiding amniocentesis and biochemical tests for pulmonary surfactant.